Partisipasi Calon Mahasiswa di Luar Jawa dalam Proses Penerimaan Mahasiswa Baru Tahun 2024 Melalui Jalur Ujian Masuk Perguruan Tinggi Keagamaan Islam Negeri - Rosihon Anwar; Mohamad Irfan; Ilham Nurjaman (UIN Sunan Gunung Djati Bandung, 2026)
This study discusses prospective students' participation in the 2024 State Islamic Higher Education Entrance Examination (UM-PTKIN), focusing on the geographical distribution of participants from various provinces in Indonesia. The method used is descriptive statistical analysis to identify patterns and disparities in prospective student participation between regions. The results show that provinces on the island of Java, such as East Java, Central Java, and West Java, dominate the number of participants, contributing to almost half of the total UM-PTKIN 2024 participants. Outside of Java, provinces such as South Sulawesi and North Sumatra also recorded fairly high participation rates, indicating a significant contribution from regions with relatively good access to education. Conversely, participation in eastern Indonesia, such as Papua and Papua Pegunungan, remains very low, influenced by limited educational infrastructure and access to technology. To increase participation in disadvantaged regions, this study recommends improving access to educational infrastructure, developing adequate facilities, and providing academic guidance programs and special scholarships for students from areas with low participation. In addition, improving access to information and socialization regarding UM-PTKIN registration procedures is also considered important to reach prospective participants in remote areas. Challenges related to data availability were also identified, and it was recommended that participation data for the past 3-5 years be collected to enable analysis of developments and predictions of future participation. These findings are expected to serve as a reference for policymakers to improve equitable access to religious higher education in Indonesia.